MODERASI BERAGAMA DALAM NOVEL "KAMBING DAN HUJAN" KARYA MAHFUD IKHWAN - Lestari, Erawati Dwi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
This study examines the form of religious moderation in the novel Kambing dan Hujan (KH) by Mahfud Ikhwan. This type of research is qualitative, which utilizes descriptive and analytical methods. The approach used is the sociology of literature which prioritizes literary texts as the study material. The results showed that the social setting of the novel KH includes people's living habits, traditions, and religious views. Meanwhile, the author's social background includes the place of birth, residence, and profession that influenced the publication of the novel KH. The social setting of the novel depicts an extreme and fanatical society in religion. However, there is also a picture of people who view everything as normal, not excessive, moderate, and do not feel superior to other parties on the opposite side. From the author's social background, it can be seen that Mahfud Ikhwan as a writer positions himself as a neutral party. Although the novel KH has a big theme, namely about two very important differences in ideology, opinions, and worship practices between NU and Muhammadiyah, the author is able to reach the two largest Islamic organizations in Indonesia's point of view by being in the middle of the two.Keywords: Sociology of Literature, Religious Moderation, The Novel Kambing dan Hujan.